KEKUATAN INOVASI DALAM PERUBAHAN KEHIDUPAN MASYARAKAT - Wijayanti, Wiwik (Dinamika Pendidikan, 2009)
Change means the innovation, and change can only be done by innovation inclusive of change in education or school passing education programs.  Orientfrom innovation infact is application conception the development lip at repair. Innovate to mean the completion adaptation, and process the adjusment (of) up at better. Exist a school change is reviseing and repair conducted by school like  curriculum repair, source learn, the study process, organization  structure, and school environment which condusive and safety. Equally, that innovation mean the change lip at secure and prosperous many people. Change of societ» having an effect on to innovation, lor example because of automatization, urbanization,  change in labor market, cultural conflict, and medical progress and also biologis. Others, there is also ethical change and religion values in society will have an effect on also TO innovation, its/or like; media, transportation, journey  and involvement international. As/or bases required in innovation cover: individual difference, self concept, self   responsibility, skill develpoment, relevansi. inquiri,    social responsibility, humanism, and all life acrompllshment have to be fullfilled   as adjusment  effort  with the science growth and technological. Key word: Innovation and education.